Methylation marker analysis of self‐sampled cervico‐vaginal lavage specimens to triage high‐risk HPV‐positive women for colposcopy. Issue 4 (28th January 2014) - Hesselink, A.T.; Heideman, D.A.M.; Steenbergen, R.D.M.; Gök, M.; van Kemenade, F.J.; Wilting, S.M.; Berkhof, J.; Meijer, C.J.L.M.; Snijders, P.J.F.
<x xml:space="preserve">Abstract</x> Methylation markers were studied for their suitability to triage human papillomavirus (HPV)‐positive women by testing self‐collected cervico‐vaginal lavage specimens. For this purpose, we analyzed 355 hrHPV‐positive self‐collected specimens with three methylation markers, that is, CADM1‐m18, MAL‐m1 and miR‐124‐2 by quantitative methylation‐specific PCR. The areas under the receiver‐operating characteristic (ROC) curve for end‐point cervical intraepithelial neoplasia grade 3 or worse (CIN3+) were 0.637 for CADM1‐m18, 0.767 for MAL‐m1 and 0.762 for miR‐124‐2. This indicates that CADM1‐m18 is not suitable as single marker. By varying the thresholds of both markers in the bi‐marker panels CADM1‐m18/MAL‐m1, CADM1‐m18/miR‐124‐2 and MAL‐m1/miR‐124‐2 upper and lower ROC curves were obtained, depicting the maximum and minimum CIN3+ sensitivity, respectively, at given specificity. For all these bi‐marker combinations, the upper curves were similar. However, for the MAL‐m1/miR‐124‐2 panel, the distance between upper and lower ROC curves was closest and this panel displayed the highest assay thresholds, indicating that this combination was most robust. At clinical specificities of 50 and 70%, the MAL‐m1/miR‐124‐2 sensitivity for detection of CIN3+ ranged from 77.0 to 87.8% and from 64.9 to 71.6%, respectively. At 70% specificity thresholds no carcinomas were missed. By comparison, the CIN3+ sensitivity of HPV16/18 genotyping on the self‐sampled lavage specimens was 58.1% (95%CI: 46.6–68.8) at a specificity of 87.7% (95%CI: 83.2–91.2). In conclusion, methylation analysis is a promising triage tool that in combination with HPV‐DNA testing offers feasible, full molecular screening on self‐collected cervico‐vaginal lavage specimens.